Rhetoric of femininity : female body image, media, and gender role stress/conflict - Pompper, Donnalyn, 1960- (Lexington studies in contemporary rhetoric., 2016)
This book offers a rhetorical examination of how femininity is defined and portrayed across media and popular culture. To do so, Pompper analyzes interviews with women representing multiple age, ethnic, and sexual orientation groups.